Spectrophotometric Method for the Determination of Mebendazol in Different Formulation - Yusra M.S.Al-Shaker, Dawood H. Mohammed, Hadeel Mustafa Abdalkader (Pakistan Journal of Medical & Health Sciences, 2022)
This research presents a new spectrophotometric method used to determine mebendazole using oxidation and coupling reaction. This method is based on using potassium chromate as an oxidizing agent for catechol, which is then combined with imibendazole to form a stable product with brown color. The highest absorption is achieved at 402 nm. Moreover, absorbance coefficient is 1556.0794 l.mol-1.cm-1. Beer’s law limits were (4-140) µg/ml.